Women's perceived support of parents and parents-in-law in China: Socioeconomic resources, reciprocity, and family context. (April 2021) - Lee, Trevor Tsz-lok; Luo, Xing
Filial support has been recognized as a main source of social support for China's aging population. While traditional Chinese families generally adhere to patrilineal, patriarchal, and patrilocal principles, there have been signs of an emerging trend of a complex, bilateral family system that has influenced the ways in which married women support elderly family members, both natal kin and in-laws, in contemporary China. However, little research exists focusing on the perspectives of married women in China on intergenerational support. Drawing on nationally representative data from the Chinese General Social Survey, this study investigates the patterns and determinants of women's financial and instrumental support of their parents and parents-in-law in China. The main results show that, while education and income separately affect women's support patterns, their husband's income level is the crucial factor determining women's financial support for parents and parents-in-law. In terms of instrumental support, norms of reciprocity are evident between women and parents/parents-in-law. Despite a positive association between financial support that women give to parents-in-law and that which they receive from parents-in-law, women's financial support tends to be less frequent when their own parents have financially supported them. The implications of these findings for our understanding of intergenerational support mechanisms and for future research are discussed.